Mechanical power and normalized mechanical power in pediatric acute respiratory distress syndrome - Shaikh, Farhan A. R.; Ramaswamy, Karthik N.; Chirla, Dinesh K.; Venkataraman, Shekhar T.; Kneyber, Martin C. J. (Frontiers in Pediatrics, 2024)
Background: Mechanical power (MP) describes energy transmitted over time to the respiratory system as a unifying determinant of ventilator-induced lung injury. MP normalization is required to account for developmental changes in children. We sought to examine the relationship between Mechanical Energy (MEBW), MP normalized to body weight (MPBW) and normalized to respiratory compliance (MPCRS) with paediatric acute respiratory distress syndrome (pARDS) severity and outcome. Method: In this retrospective study, children aged one month to 18 years with pARDS, on the pressure-control ventilation mode for at least 24 hours between January 2017 and September 2020, were enrolled. We calculated MP using Becher's equation. Multivariable logistic regression analysis adjusted for age, pediatric organ dysfunction score, and oxygenation index (OI) was performed to determine the independent association of MP and its derivatives 24 hours after diagnosing pARDS with 28-day mortality.The association was also studied for 28 ventilator-free days (VFD-28) and the PARDS severity in terms of OI. Results: One-hundred and eighty-five patients were eligible out of 246 admitted with PARDS, with an overall mortality of 43.7%. Non-survivors had higher severity of illness, MP, MPBW, and MEBW. Multivariable logistic regression analysis showed that only MEBW but not MP, MPBW or MPCRS at 24 hours was independently associated with mortality (adjusted OR:1.072(1.002-1.147), p-0.044). However, after adjusting for the type of pARDS, MEBW was not independently associated with mortality (adjusted OR:1.061(0.992-1.136),p-0.085). After adjusting for malnutrition, only MP at 24 hours was found to be independently associated. Only MPCRS at 1-4 hrs and 24 hrs but not MP, MPBW or MEBW at 24 hours of diagnosing pARDS significantly correlated with VFD-28. Conclusions: Normalization of MP is better related to outcomes and severity of pARDS than non-normalized MP. Malnutrition can be a significant confounding factor in resource-limited settings.